Pengaruh Bahan Pengemas dan Lama Simpan Terhadap Mutu Tepung Tapioka - Suismono Suismono; Suharmadi Suharmadi; Agus Setyono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1989)
Five bags of different packaging materials were used to pack tapioca starch. The packages were then stored for six months. Proximate composition and physical characteristics of the starch were analysed monthly. It was found that packing in either polyethylene bag or polyethylene bag covered with polypropylene bag gave better quality starch than packing in either gunny or polypropylene bags.